Passivity Based Attitude Control of Rigid Bodies. Issue 3 (18th March 2013) - Wang, Hanlei; Xie, Yongchun
Abstract In this paper, we present a tutorial on passivity based attitude control that has been investigated over the past two decades. Both regulation control and adaptive tracking control for the attitude motion of rigid bodies are discussed under a unified passivity framework. Our attention is mainly confined to the attitude control schemes that are based on the passivity notion. Output feedback attitude control, attitude synchronization, and some open problems are also discussed.